Australia : Selected Issues. (IMF Staff Country Reports; Country Report, 2011)
This study relates Australian household saving more closely to movements in asset market using event study analysis and econometric analysis. In this study, the policy challenges for Australia from rebalancing in China, a temporary growth slowdown in China, and a recession in advanced countries are analyzed. The Globally Integrated Monetary and Fiscal Model (GIMF) is used for policy challenges. The impact of the mining boom on the Australian labor market is also discussed in this paper.